Cancellation of clutter and multipath in passive radar using a sequential approach - Colone, F.; Cardinali, R.; Lombardo, P. (2006 IEEE Conference on Radar, 2006)
The paper deals with the cancellation of direct signal, multipath and clutter echoes in passive radar, where the transmitted waveform is not under control of the radar designer and the sidelobes of the ambiguity function mask even targets largely displaced in range and Doppler from the disturbance. A sequential approach is presented for disturbance cancellation and target detection based on projections of the received signals in a subspace orthogonal to both disturbance and previously detected targets. Modeling the clutter spread on few Doppler bins allows complete clutter cancellation. The approach is shown to be effective against typical scenarios with a limited number of iterations.